Pengaruh Kualitas Layanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada JNT Expres Cabang Batam - Eka Rahma Safitri; Mauli Siagian (SCIENTIA JOURNAL, 2024)
This research aims to investigate the influence of service quality and customer satisfaction on customerloyalty at JNT Express Batam branch. The population to be studied are customers who have used the JNTExpress goods delivery service at the Tanjung Piayu branch in August 2023, totaling 60,203 customers. Thesampling technique can be used using the Slovin formula which has produced 397 respondents. The dataanalysis process uses a multiple linear regression approach, which includes testing data quality tests,classical assumption tests, influence tests and hypothesis tests. The results of multiple linear regressionanalysis show that service quality has an influence of 28.4% on customer loyalty. Customer satisfaction hasan influence of 35.0% on customer loyalty. Findings from the coefficient of determination (R2) show thatoverall, service quality and customer satisfaction can explain 65.1% of the variation in customer loyalty. Inaddition, the t test and F test show that both service quality and customer satisfaction have a positive andsignificant influence partially or simultaneously on customer loyalty at JNT Express Batam branch